General strategy for a short and efficient synthesis of 3-hydroxy-4-methylprolines (HMP) - Mohapatra, Debendra K.; Mondal, Dhananjoy; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The non-proteinogenic amino acid 3-hydroxy-4-methylproline (HMP) is an active constituent of some potent antimicrobials including echinocandins, nostopeptins, pneumocandins, sporiofungin and mulundocandins. A synthesis has been achieved in 10 steps with 29% overall yield; the Evans' aldol reaction using Crimmins' modified method was pivotal to the success of the strategy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 3; 4-disubstituted proline; Crimmins' aldol reaction; Garner's aldehyde; non-proteinogenic amino acids; RUO4 mediated oxidation